(untitled) (Portuguese Journal of Family Medicine and General Practice, 2009)
Often, children and adolescents complain of knee pain, leading parents to take them to a clinical consultation with their family physician. The frequency of knee pain is considerable but only occasionally does the knee have an injury that needs surgery. Therefore it is very important to understand what type of knee pain is being referred. It is also important to know that there are significant differences between the knee of a children (and an adolescent) and that of an adult. The goal of this article is to outline a practical approach for the evaluation and treatment of knee pain in children and adolescents.